Implementasi Panggung TV Sekolah Sebagai Media Pembelajaran di RA Mutiara Ambon - Rohana; Sri Watini (EDUKASIA: Jurnal Pendidikan dan Pembelajaran, 2022)
School TV is one of the innovations made by the nation's children as the best breakthrough based on digital space for learning and creativity. School TV can be used as a digital-based learning media that can be accessed via the tvschool.id link. There are several main features in School TV, namely the choice of school stage, digital library, school TV festival and virtual classroom. School TV is used as a medium for Early Childhood learning activities that can be used from school institutions, teachers and principals. The school TV stage is a medium of learning at RA Mutiara Ambon, which is located at Jln Laksdya Leo Wattimena, Waiheru Village, BTN Perumnas Block II, Baguala District, Ambon- Maluku. This study uses a qualitative descriptive method with data collection techniques using observations, interviews, documentation, and field notes. The research topic that is focused on is the implementation of the school TV stage as a learning medium at RA Mutiara Ambon. The first digital learning media is used by Mutiara school for Early Childhood learning activities.